Evolving populations of the potato late blight pathogen Phytophthora infestans - does climate change matter? - Andrivon, Didier; Andersson, Björn; Hannukkala, Asko; Hermansen, Arne; Hansen, Jens G (MTT, 2007)
Global warming and correlative changes in local and mesoclimatic conditions are now widely accepted as one of the striking features of the last few decades. These changes are forecasted to persist well into the 21st century, and have already been held responsible for major changes in the distribution of plant and animal species, pathogen prevalence, and pest biodiversity. However, we still lack a comprehensive understanding of the ways climate change might affect major plant diseases, although speculation as to their implication in epidemiological and evolutionary changes have been raised. This paper will focus on potato late blight, a major disease, caused by the oomycete Phytophthora infestans. This pathosystem is well suited to investigate climate change issues, because 1) the pathogen is strongly dependent on climatic factors (mainly temperature and moisture duration) for infection and sporulation, 2) the pathogen has been present in Europe since more than a century and a half, and its epidemics are closely monitored in most European countries, 3) the pathogen and its hosts (potato and tomato) are widely distributed in Europe, over a large range of latitudes and longitudes, 4) the population structures of the pathogen have undergone dramatic changes over the past 30 years following a secondary introduction from the American continent, and 5) both phenotypic and molecular tools are available to follow the evolutionary and adaptive changes in these populations. We will address three main questions, for which data are either already available or urgently needed: 1- initiation of epidemics - are they earlier, and if yes, how much of it is due to changes in climate? A recent paper, exploiting long term surveys of late blight incidence and correlations with climatic and agronomic data in Finland shows that the first detection of late blight outbreaks is now approximately one month earlier than it was 20 years ago, and that the occurrence of late blight outbreaks in the northern parts of the country is considerably more frequent now than it was in the past. This is convincing evidence that climate change is important as a driver for earlier and/or more severe epidemics in regions previously not highly conducive to late blight. 2- aggressiveness changes - are these related to new climatic conditions, or at least do current climatic conditions favor different strains than the 'classical ones'? There is scattered evidence, both direct and indirect, that current populations of P. infestans might be able to thrive at lower threshold temperatures. However, these data are still insufficient to conclude that populations have adapted to more variable climates. Recent work also showed that aggressiveness might have increased as a consequence of adaptation to prevailing cultivars, with no climatic driver required. 3- oospore distribution and climate zones. Because oospores are resting organs, it is plausible that they will be found more often in areas with either short crop cycles and/or extreme seasons (winter or summer). A preliminary exploitation of the data collected within the EUCABLIGHT database suggest a correlation between frozen soil conditions and the presence of oospore problems. However, populations with both mating types are now becoming common also in temperate, atlantic regions such as northern France or the UK, so cold seasons are certainly not the only factor favouring the survival of mixed populations.
Keywords: Ta; Ka; kasvinsuojelu; kasvitaudit; peruna; perunarutto; Phytophthora infestans; plant protection; Phytophthora infestans